2019
DOI: 10.1007/s00787-019-01358-w
|View full text |Cite
|
Sign up to set email alerts
|

The nature and extent of emotion recognition and empathy impairments in children showing disruptive behaviour referred into a crime prevention programme

Abstract: Childhood disruptive behaviour has been linked to later antisocial and criminal behaviour. Emotion recognition and empathy impairments, thought to be caused by inattention to the eye region, are hypothesised to contribute to antisocial and criminal behaviour. This is the first study to simultaneously examine emotion recognition and empathy impairments, their relationship, and the mechanism behind these impairments, in children with disruptive behaviour. We hypothesised that children with disruptive behaviour w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 49 publications
1
35
0
1
Order By: Relevance
“…The Research Domain Criteria (RDoC) approach [26] advocates the study of underlying and transdiagnostic processes involved in mental health problems and the development of personalised interventions targeting those with clear problems, rather than assuming that impaired processes are present in all those sharing a diagnosis or exhibiting similar behavioural problems. In line with this approach, it has been established that emotion recognition can be rapidly improved in children with behavioural problems [23]. Building on this work, in the current study we aimed to examine the longer-term effects of an emotion recognition training on behaviour and mental health 6 months later, as rated by teachers who were unaware which children had received emotion training.…”
Section: Introductionmentioning
confidence: 99%
“…The Research Domain Criteria (RDoC) approach [26] advocates the study of underlying and transdiagnostic processes involved in mental health problems and the development of personalised interventions targeting those with clear problems, rather than assuming that impaired processes are present in all those sharing a diagnosis or exhibiting similar behavioural problems. In line with this approach, it has been established that emotion recognition can be rapidly improved in children with behavioural problems [23]. Building on this work, in the current study we aimed to examine the longer-term effects of an emotion recognition training on behaviour and mental health 6 months later, as rated by teachers who were unaware which children had received emotion training.…”
Section: Introductionmentioning
confidence: 99%
“…The children in the BP group did not have a formal mental health diagnosis and their behavioural and/or emotional problems were confirmed by teacher report via the Strengths and Difficulties Questionnaire (SDQ; Goodman 1997). Children scoring in above average range for conduct and/or peer problems (≥ 3 out of 10) and/or below average range for prosocial behaviour (≤ 5 out of 10) were eligible to be included in the BP group (see Hunnikin et al 2019, for a detailed description of the eligibility criteria). Children in the TD group were referred by their teachers for not showing behavioural or emotion problems.…”
Section: Participantsmentioning
confidence: 99%
“…The Facial Emotion Recognition (FER; Hunnikin et al 2019) test was used to measure children's ability to recognise faces displaying happy, sad, fearful, angry and neutral expressions. Children viewed 60 faces on a laptop displaying one of the five expressions at either a low or a high intensity.…”
Section: Facial Emotion Recognitionmentioning
confidence: 99%
“…There is considerable evidence that antisociality is characterised by emotional processing impairments, such as reduced empathy, lower physiological affective responsivity, diminished capacity to learn about punishment and reward, and emotional dysregulation (K. Blair, Morton, Leonard, & Blair, 2006;R. Blair, 1999;Fanti et al, 2019;Gao, Raine, Venables, Dawson, & Mednick, 2010;Hunnikin, Wells, Ash, & Van Goozen, 2019;Van Goozen, Fairchild, Snoek, & Harold, 2007;Van Langen, Wissink, Van Vugt, Van der Stouwe, & Stams, 2014). Using magnetic resonance imaging (MRI), studies have identified structural and functional abnormalities in limbic brain regions important for processing emotion, in particular the amygdala, and prefrontal regions implicated in affective decision-making, learning and regulation, such as the orbitofrontal and ventromedial prefrontal cortex (Baker, Clanton, Rogers, & De Brito, 2015;Coccaro, McCloskey, Fitzgerald, & Phan, 2007;Meyer-Lindenberg et al, 2006;Noordermeer, Luman, & Oosterlaan, 2016;Pardini, Raine, Erickson, & Loeber, 4 2014;Rogers & De Brito, 2016;Thomas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%